Pivotal Role of Tenascin-W (-N) in Postnatal Incisor Growth and Periodontal Ligament Remodeling - Imhof, Thomas; Balic, Anamaria; Heilig, Juliane; Chiquet-Ehrismann, Ruth; Chiquet, Matthias; Niehoff, Anja; Brachvogel, Bent; Thesleff, Irma; Koch, Manuel (Frontiers in Immunology, 2021)
The continuously growing mouse incisor provides a fascinating model for studying stem cell regulation and organ renewal. In the incisor, epithelial and mesenchymal stem cells assure lifelong tooth growth. The epithelial stem cells reside in a niche known as the cervical loop. Mesenchymal stem cells are located in the nearby apical neurovascular bundle and in the neural plexus. So far, little is known about extracellular cues that are controlling incisor stem cell renewal and guidance. The extracellular matrix protein tenascin-W, also known as tenascin-N (TNN), is expressed in the mesenchyme of the pulp and of the periodontal ligament of the incisor, and is closely associated with collagen 3 fibers. Here, we report for the first time the phenotype of tenascin-W/TNN deficient mice, which in a C57BL/6N background exhibit a reduced body weight and lifespan. We found major defects in the alveolar bone and periodontal ligament of the growing rodent incisors, whereas molars were not affected. The alveolar bone around the incisor was replaced by a dense scar-like connective tissue, enriched with newly formed nerve fibers likely leading to periodontal pain, less food intake and reduced body weight. Using soft food to reduce mechanical load on the incisor partially rescued the phenotype. In situ hybridization and Gli1 reporter mouse experiments revealed decreased hedgehog signaling in the incisor mesenchymal stem cell compartment, which coordinates the development of mesenchymal stem cell niche. These results indicate that TNN deficiency in mice affects periodontal remodeling and increases nerve fiber branching. Through periodontal pain the food intake is reduced and the incisor renewal and the neurovascular sonic hedgehog secretion rate are reduced. In conclusion, tenascin-W/TNN seems to have a primary function in rapid periodontal tissue remodeling and a secondary function in mechanosensation.